Near-coastal water quality at reference sites following storm events. Issue 1 (15th February 2016) - Schiff, Kenneth; Brown, Jeff; Trump, Steen; Hardin, Dane
Abstract: Stormwater is a challenging source of coastal pollution to abate because stormwater also involves complex natural processes, and differentiating these processes from anthropogenic excesses is difficult. The goal of this study was to identify the natural concentrations of stormwater constituents along the 1377 km coastline of California, USA. Twenty-eight ocean reference sites, a priori defined by lack of human disturbance in its adjacent watershed, were collected following 78 site-events and measured for 57 constituents and toxicity. Results indicated a complete lack of toxicity and undetectable levels of anthropogenic constituents (i.e., pesticides). The range of concentrations in ocean receiving waters for naturally-occurring constituents (i.e., total suspended solids, nutrients, trace metals) typically ranged three orders of magnitude. Regional differences and storm characteristics did not explain much of the variations in concentration. The reference site information is now being used to establish targets for marine protected areas subject to runoff from developed watersheds. Highlights: This study identified the natural concentrations of stormwater constituents along the 1, 377 km coastline of California, USA Results indicated a complete lack of toxicity and undetectable levels of human synthetic constituents (i.e., pesticides) Concentrations of naturally occurring constituents (i.e., TSS, metals) ranged orders of magnitude in ocean receiving waters Regional differences and storm characteristics did not explain much of the variation in concentration These results are now being used to establish concentration targets for marine protected areas